Guidelines on the treatment with integrated traditional Chinese medicine and western medicine for severe coronavirus disease 2019. (December 2021) - Li, Zhi-Yu; Xie, Zhi-Jun; Li, Hai-Chang; Wang, Jian-Jian; Wen, Xiang-Hui; Wu, Shou-Yuan; Chen, Jiao; Zhang, Juan-Juan; Li, Lin; Guo, Qiang-Qiang; Liu, Qiu-Ping; Lan, Hui; et al.
Abstract: Severe Coronavirus Disease 2019 (COVID-19) is characterized by numerous complications, complex disease, and high mortality, making its treatment a top priority in the treatment of COVID-19. Integrated traditional Chinese medicine (TCM) and western medicine played an important role in the prevention, treatment, and rehabilitation of COVID-19 during the epidemic. However, currently there are no evidence-based guidelines for the integrated treatment of severe COVID-19 with TCM and western medicine. Therefore, it is important to develop an evidence-based guideline on the treatment of severe COVID-19 with integrated TCM and western medicine, in order to provide clinical guidance and decision basis for healthcare professionals, public health personnel, and scientific researchers involved in the diagnosis, treatment, and care of COVID-19 patients. We developed and completed the guideline by referring to the standardization process of the "WHO handbook for guideline development", the Grading of Recommendations Assessment, Development and Evaluation (GRADE) system, and the Reporting Items for Practice Guidelines in Healthcare (RIGHT). Graphical Abstract: ga1